Faktor-Faktor Mengoptimalkan Kecerdasan Spiritual Anak Menurut Amsal 1:1-7 - Tarigan, Berta Br; Imeldawati, Tiur; Laoli, Deslimawati (STT Injili Indonesia Medan, 2022)
Spiritual intelligence is the most important and main thing in human life, especially for children, therefore to optimize children's spiritual intelligence should be based on the Word of God. Proverbs 1:1-7 is a fundamental factor and especially in optimizing a child's spiritual intelligence, namely: Fear of God, have wisdom, accept every education, understand meaningful words, live righteously, justly, honestly and wisely. Other factors are the role of parents, the role of the church and the role of the school,Keywords: spiritual intelligence, optimizing, fearing God, role